Design of a Gravity Acceleration Measurement System Using a Pendulum Oscillation Tool and Tracker Analysis - Annisa Permata; Asrizal Asrizal; Harman Amir; Mona Sari (Journal of Experimental and Applied Physics, 2026)
Experiment has a crucial role in physics, one of the fundamental science for research and technology. This research focuses on gravitation and utilizes methods of experimental design and execution. Measuring gravitation is a frequently studied topic and related to the oscillation pendulum's harmonic. In practice, pendulum oscillations are often still calculated manually without visualizing the pendulum's trajectory during oscillation. With modern learning tools development, harmonic oscillations' measurements can be calculated and analysed by using video tracking software, for example, by generating graphs. A static pendulum with a string in three lengths: 50 cm, 60 cm, and 70 cm is required. The swinging pendulum loaded with a 100-gram weight and filmed by a camera. The recordings were analysed using the tracker software. The results were displayed as a sinusoidal waveform plotted from the points along the pendulum's path during oscillation.